ENDOGENEIZATION OF THE CRITERIA OF AN OPTIMAL MONETARY ZONE IN THE CONTEXT OF ECOWAS COUNTRIES: FINANCIAL INTEGRATION CHANNEL - (:unkn) unknown (My University, 2022)
The year 1990 marks the emergence of a new approach to the theory of Optimal Currency Areas and formalized under the name of the theory of endogenous criteria. According to Labondance (2011), this theory has modified the field of investigation of the formation of optimal monetary unions of Mundell (1961) and is oriented towards the development of studies in terms of endogenization, the most famous of which is the phenomenon of endogeneity of Frankel and Rose (1998).Our thesis, in the light of this theory of endogenous criteria, makes an empirical contribution to the asynchronous characteristics of the economic cycles of the candidate states of the ECOWAS monetary project, by proposing an adjustment mechanism for asymmetric shocks. Indeed, the study examines the potential effect of financial integration on the level of synchronization of real cycles in West African countries. We adopt an econometric approach based on panel procedures and the two-step generalized method of moments (GMM-system) over the period [1990-2016]. On the one hand, we show that trade integration remains associated with a reconciliation of the cyclical fluctuations of West African economies and the similarity of economic policies does not affect the co-evolution of the cycles of these countries. On the other hand, the heterogeneity of the financial system is associated with a reduced coherence of the economic cycles of the member countries of the ECOWAS monetary project. In other words, a deepening of financial ties is linked to more synchronized real cycles. In addition, the positive impact of sharing a single currency on the symmetry of cycles through the reconciliation of financial structures is attested by WAEMU. Therefore, the level of synchronization of business cycles could improve with the strengthening of financial circuits, after the launch of the single currency of West African states. This implies proximity to economic cycles ex-post and a phenomenon of endogeneity thro
Keywords: African Research